2022
DOI: 10.3389/fchem.2022.937180
|View full text |Cite
|
Sign up to set email alerts
|

A Combination of Membrane Filtration and Raman-Active DNA Ligand Greatly Enhances Sensitivity of SERS-Based Aptasensors for Influenza A Virus

Abstract: Biosensors combining the ultrahigh sensitivity of surface-enhanced Raman scattering (SERS) and the specificity of nucleic acid aptamers have recently drawn attention in the detection of respiratory viruses. The most sensitive SERS-based aptasensors allow determining as low as 104 virus particles per mL that is 100-fold lower than any antibody-based lateral flow tests but 10–100-times higher than a routine polymerase chain reaction with reversed transcription (RT-PCR). Sensitivity of RT-PCR has not been achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 38 publications
(69 reference statements)
0
16
0
Order By: Relevance
“…RHA0385 aptamer was chosen as a recognizing element of the sensor, since it was shown to have high affinity and selectivity towards the influenza A virus ( Zhdanov et al, 2022b ). The dissociation constant of the complex between RHA0385 and influenza A hemagglutinin is 0.6 nM ( Bizyaeva et al, 2021 ); and the dissociation constant of the complex between RHA0385 and influenza A virus is as low as 1.1 pM ( Zhdanov et al, 2022b ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…RHA0385 aptamer was chosen as a recognizing element of the sensor, since it was shown to have high affinity and selectivity towards the influenza A virus ( Zhdanov et al, 2022b ). The dissociation constant of the complex between RHA0385 and influenza A hemagglutinin is 0.6 nM ( Bizyaeva et al, 2021 ); and the dissociation constant of the complex between RHA0385 and influenza A virus is as low as 1.1 pM ( Zhdanov et al, 2022b ).…”
Section: Resultsmentioning
confidence: 99%
“…Biological media are challenging for SERS-based sensors as non-specific adsorption of biomolecules drastically decreases the signals from the target molecules. For example, blood plasma is to be diluted at least 1,000-times for colloidal SERS-sensors ( Zhdanov et al, 2022a ), whereas the effect from impurities of the allantoic fluid was observed even after 10 6 -times dilution with a buffer ( Zhdanov et al, 2022b ). Membrane filtration makes the task much easier for decreasing the concentration of non-specific compounds.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, aptamer-based analysis methods have been actively developed due to their low cost, high stability, ease of modification, and superior specificity and affinity. Combining the surface enhancement of Raman scattering and luminescence with molecular recognition through aptamers has a promising future as it allows to create effective and inexpensive sensor designs for detecting molecular targets of various nature, such as low-molecular-weight compounds [ 23 ], protein toxins [ 24 ], bacteria [ 25 ], viruses [ 12 , 26 ], and circulating cancer cells [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%